Bernard Riemann's gesammelte mathematische Werke und wissenschaftlicher Nachlass - Riemann, Bernhard 1826-1866 (Cambridge library collection. Mathematics, 2013)
Great mathematicians write for the future and Georg Friedrich Bernhard Riemann (1826-66) was one of the greatest mathematicians of all time. Edited by Heinrich Martin Weber, with assistance from Richard Dedekind, this edition of his collected works in German first appeared in 1876. Riemann's interests ranged from pure mathematics to mathematical physics. He wrote a short paper on number theory which provided the key to the prime number theorem, and his zeta hypothesis has given mathematicians the most famous of today's unsolved problems. Moreover, his famous 1854 lecture 'On the hypotheses which underlie geometry' set in motion studies which culminated in Einstein's general theory of relativity. Even Riemann's over-optimistic use of the Dirichlet principle to prove the conformal mapping theorem turned out to be immensely fruitful. The alert reader will further profit from finding here the seeds of modern distribution theory, algebraic topology and measure theory.